Meningkatkan Hasil Belajar Peserta Didik Melalui Pembelajaran Problem Based Learning di SDN 33 Gurun Panjang - Pitriyani Pitriyani (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education (PAI) for grade V at SDN 33 Gurun Panjang through the implementation of the Problem-Based Learning (PBL) model. This Classroom Action Research (CAR) was conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The results showed a significant improvement in students' learning outcomes, with learning mastery increasing from 37.5% in the pre-cycle to 56.25% in the first cycle and reaching 87.5% in the second cycle. The PBL approach motivated students to actively participate in the learning process through group discussions and real-world problem-solving. This success was supported by the teacher's role as a facilitator, increased student engagement, and engaging teaching strategies. The study concludes that PBL is effective in improving students' learning outcomes while creating an interactive and enjoyable learning environment.